The role of the gut microbiota and the use of new therapies in Irritable Bowel Syndrome - Dąbrowski, Jan; Gąbka, Ilona; Dalmata, Weronika; Gendek, Karolina; Kozłowska, Anna; Korzeniowska, Anna; Załęska, Natalia (Journal of Education, Health and Sport, 2023)
Introduction: Irritable bowel syndrome is a functional disorder of the gastrointestinal tract with a multifactorial nature of the disease. IBS affects 11% of the population, with the gut microbiota playing an important role in the pathophysiology. Purpose: The aim of this article is to present the course of irritable bowel syndrome, the role of the gut microbiota in pathophysiology, and new therapeutic approaches, including probiotics, based on the current state of knowledge. Conclusions: IBS is a syndrome whose exact pathophysiology is not fully understood. The state of the gut microbiota has a huge impact on the course of the disease, but also on the functioning of the whole body. New therapies currently in use, i.e. probiotics, are showing promising results, but more research is needed to find the golden mean to treat the disease. Methods: Data for the article were retrieved using PubMed setting the time descriptors to 2013-2023. Irritable bowel syndrome is one of the more common functional disorders of the gastrointestinal tract. It manifests as recurrent abdominal pain, discomfort and bloating accompanied by bowel movements without a direct underlying cause. From multicentre clinical studies, it is known that disorders of various mechanisms within the brain-gut axis, altered gastrointestinal motility and visceral hypersensitivity are the underlying causes. In addition, many scholars are of the opinion that disturbances in the gut microbiota play a key role in the pathogenesis of IBS.